E' Gadung': a game application to promoting kimaragang folklore - Lilian Lee Shiau Gee; Victor B. Pangayan (2021)
Folklore is an integral aspect of cultural inheritance and Sabahan's need to keep their cultural heritage preserved. The beauty of Sabah's ethnic folklore is that they are part of an indigenous heritage that reflects their own cultural identity, which is passed down orally through centuries. But the younger generation increasingly forgets this heritage. The interactive games seek to safeguard cultural heritage that has been displaced in daily life. Hence, along with the interactive gaming environment, a dedicated effort to bring and promote them to young people. 'E’ Gadung' was developed to promote Kimaragang folklore in an attempt to increase understanding of traditional culture. The 'E’ Gadung' concept began with the transcription of the oral tradition tale into gameplay mechanic and game character, while the scenario and objects imitate the Kimarang costume and culture via computer graphics software. 'E’ Gadung' was built in four main processes based on the iterative game model (design, implementing, playtest and evaluate). The 'E’ Gadung' prototype was seen with fixed bug and high interactions through a series of game tests. The 'E’ Gadung' prototype has great potential and ability to connect ideas and motivate players to understand local Sabah folklore. The ‘E’ Gadung’ provides tremendous experience, recognition and artistic creation of a new perspective towards Sabah Folktales in the context of learning to increase the cultural knowledge of folktales among younger generations.